Treatment strategies for patients with advanced ovarian cancer undergoing neoadjuvant chemotherapy: interval debulking surgery or additional chemotherapy? - Yoneoka, Yutaka (J Gynecol Oncol, 2019)
OBJECTIVE: To treat advanced ovarian cancer, interval debulking surgery (IDS) is performed after 3 cycles each of neoadjuvant chemotherapy (NAC) and postoperative chemotherapy (IDS group). If we expect that complete resection cannot be achieved by IDS, debulking surgery is performed after administering additional 3 cycles of chemotherapy without postoperative chemotherapy (Add-C group). We evaluated the survival outcomes of the Add-C group and determined their serum cancer antigen 125 (CA125) levels to predict complete surgery. METHODS: A retrospective chart review of all stage III and IV ovarian, fallopian tube, and peritoneal cancer patients treated with NAC in 2007–2016 was conducted. RESULTS: About 117 patients comprised the IDS group and 26 comprised the Add-C group. Univariate and multivariate analyses revealed that Add-C group had an equivalent effect on progression-free survival (PFS; p=0.09) and overall survival (OS; p=0.94) compared with the IDS group. Multivariate analysis revealed that patients who developed residual disease after surgery had worse PFS (hazard ratio [HR]=2.18; 95% confidence interval [CI]=1.45–3.28) and OS (HR=2.33; 95% CI=1.43–3.79), and those who received <6 cycles of chemotherapy had worse PFS (HR=5.30; 95% CI=2.56–10.99) and OS (HR=3.05; 95% CI=1.46–6.38). The preoperative serum CA125 cutoff level was 30 U/mL based on Youden index method. CONCLUSIONS: Administering 3 additional cycles of chemotherapy followed by debulking surgery exhibited equivalent effects on survival as IDS followed by 3 cycles of postoperative chemotherapy. Preoperative serum CA125 levels of ≤30 U/mL may be a useful predictor of achieving complete surgery.